Synthesis, characterization and optimization of polyacrylonitrile electrospun nanofiber membranes - Agung Mataram, 1979-; Ahmad Fauzi Ismail, 1966-; Takeshi, Matsuura; Fakulti Kejuruteraan Kimia (2012)
Thesis (Ph.D (Kejuruteraan Kimia)) - Universiti Teknologi Malaysia, 2012